Debottlenecking biomass supply chain resources deficiency via element targeting approach - Lim, C.; How, B.; Ng, Wendy; Leong, W.; Ngan, S.; Lam, H. (The Italian Association of Chemical Engineering, 2018)
Copyright © 2018, AIDIC Servizi S.r.l. Biomass has been one of the focus in research and development of renewable resources for energy, chemicals and downstream products. Despite many success of biomass conversion technologies such as pyrolysis, gasification, fermentation, and combustion, implementation of such technologies in industrial scale is often very challenging. The major limitations within the system include unique properties of each biomass species, unique regional nature of biomass system, complex supply chain and logistic distribution. Nonetheless, the demand for renewable energy and its products are favourable, increasing the need for more sustainable and green processes. However, most of the current biomass technology being implemented is only designed in relatively small scale due to limitation of local biomass resources. Availability of biomass resources has been one of the main constraint for mass production of biomass product. Element targeting approach was used in previous Biomass Element Life Cycle Analysis (BELCA) model to allow consideration of underutilised biomass based on element characteristics as alternative resources for existing conversion technologies to minimise supply chain distribution and material cost. Nevertheless, the approach only considers all of biomass species available and identified in the local region. This results in the total amount of biomass acquired within the regional area to be the bottleneck for mass production in fulfilling the increasing demand. The common rectification is to import similar biomass species from outer region to increase the resources for technology feed. In this research, a new biomass supply chain modelling approach is proposed to debottleneck the system via element targeting approach. The main advantage of the model is the investigation of the bottleneck biomass resources element characteristic properties instead of the limiting biomass species. Based on the regional biomass element characteristic deficiency, optimum biomass species or combination of biomasses can be identified for importation from outer region according to availability, logistic and cost. The proposed debottlenecking approach for biomass supply chain system enable an in-depth understanding of the resources deficiency based on the properties instead of biomass species, which allow higher flexibility in biomass importation and selectivity. This can be utilised as decision-making-tool to determine the best biomass species or combination to be imported into the regional system.